Escritas feministas: os jornais Brasil Mulher, Nós Mulheres e Mulherio (1975-1988) - Tamião, Juliana Segato (2009)
This dissertation seeks for recovering parts of the feminist movement history in Brazil in the alternative press, media vehicle that created ideas and speeches that were not completely silenced by the military government and its imposed censure. We analyzed the feminism in the national alternative feminist press by selecting the following: Brasil Mulher (1978 1980), Nós Mulheres (1976 1978) and Mulherio (1981 -1988). We tried to recover the social tensions faced by that press and, in that context, the theoretic methodological bases used by the newspapers as a whole and especially in the debate about body politics